Work-Family Conflict, Children, and Hour Mismatches in Australia - Reynolds, J; Aletraris, L (My University, 2007)
This article helps integrate research on work hours and work—family issues by examining how work—family conflict is related to the desire for more and fewer hours of work. Using the first wave of the Household Income and Labor Dynamics in Australia survey, we find that work-to-family conflict is associated with a desire for fewer hours of work. Family-to-work conflict, however, is only weakly associated with desired work hour changes, and we find some evidence that it makes women want to increase the number of hours they work. We also find evidence of moderating effects: Work-to-family conflict is more likely to make women want fewer hours when they have preschool children. We conclude that many working parents see work hour reductions as a way to cope with work—family conflict but that people prefer different coping strategies depending on their gender and family situation.
Keywords: Employment; Employment -- Hours; Families -- Work/family balance; Families -- Children; Families; Families and relationships; Labour market; Families; Employment; Hours; Work/family balance; Children; Employment and unemployment; Families and relationships